KESIAPAN DOKTER UMUM UNTUK PELAYANAN KACAMATA DI FASILITAS KESEHATAN TINGKAT PERTAMA DI KOTA MATARAM, NUSA TENGGARA BARAT - Isna Kusuma Nintyastuti (Faculty of Medicine Universitas Mataram, 2021)
Refractive errors are cases of eye disease with competency level 4 based on the 2012 Indonesian Doctor Competency Standards (SKDI). If the facilities and competencies are ready, refractive errors would no longer need to be referred to ophthalmologists. The application of the competency in the practice of general practitioners (GPs) has never been recorded. Therefore, a study was needed regarding the readiness of GPs to give that service in First Level Health Facilities (FKTP). Readiness needs to be assessed in terms of competence and supporting infrastructures. This study aims to determine the level of readiness of GPs in Mataram. The method used was descriptive cross-sectional. There were 28 general practitioners participated. Judging from the readiness of facilities and infrastructure, there were 7 (25%) doctors did not have a practice room with a length of 6 or 3 meters. The most widely owned equipment was Snellen optotype (85.71%), while those not owned were trial lenses (14.29%) and trial frame (10.71%). Most GPs feel competent to correct refractive errors (57.1%) but were still hesitant to provide eyeglass correction services at FKTP (53.6%). All GPs stated that they referred alls patients with refractive errors. However, most doctors (71.4%) agreed that eyeglass examination services should be available at the FKTP. In conclusion, there was still a lack of facilities and infrastructures for eyeglass correction services in most GPs' practice rooms in Mataram. General practitioners in the Mataram area felt that they are competent enough to carry out examinations and correct refractive errors.